2020
DOI: 10.3390/microorganisms8111755
|View full text |Cite
|
Sign up to set email alerts
|

Limited Genetic Diversity of blaCMY-2-Containing IncI1-pST12 Plasmids from Enterobacteriaceae of Human and Broiler Chicken Origin in The Netherlands

Abstract: Distinguishing epidemiologically related and unrelated plasmids is essential to confirm plasmid transmission. We compared IncI1–pST12 plasmids from both human and livestock origin and explored the degree of sequence similarity between plasmids from Enterobacteriaceae with different epidemiological links. Short-read sequence data of Enterobacteriaceae cultured from humans and broilers were screened for the presence of both a blaCMY-2 gene and an IncI1–pST12 replicon. Isolates were long-read sequenced on a MinIO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Previous studies have implicated highly similar IncI1 pST3 plasmids as the main mechanism of spread for bla CTX-M-1 in isolates from turkeys 21 and major production animals from Canada, 8 veal calves and humans from France, 26 , 71 food isolates from Germany, 12 wild animals from Portugal, 71 and amongst human, animal and food products in Denmark, 29 Reunion Island 30 and Japan. 28 Similarly, pST12 and pST2 bla CMY-2 subtypes were previously reported in isolates from humans, dogs and poultry in Denmark, 11 , 32 humans and chickens in the Netherlands, 27 humans, poultry and food isolates from Germany, 9 and in dogs in France. 72 , 73 Here we also found these two bla CMY-2 epidemic plasmids in multiple sources and countries.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous studies have implicated highly similar IncI1 pST3 plasmids as the main mechanism of spread for bla CTX-M-1 in isolates from turkeys 21 and major production animals from Canada, 8 veal calves and humans from France, 26 , 71 food isolates from Germany, 12 wild animals from Portugal, 71 and amongst human, animal and food products in Denmark, 29 Reunion Island 30 and Japan. 28 Similarly, pST12 and pST2 bla CMY-2 subtypes were previously reported in isolates from humans, dogs and poultry in Denmark, 11 , 32 humans and chickens in the Netherlands, 27 humans, poultry and food isolates from Germany, 9 and in dogs in France. 72 , 73 Here we also found these two bla CMY-2 epidemic plasmids in multiple sources and countries.…”
Section: Discussionsupporting
confidence: 60%
“… 45 , 46 Previous studies using only short-read data reported ESC-R plasmid subtypes, 9 , 14 , 20 and recent studies using long- and short-read data have investigated the degree to which these plasmid subtypes were conserved. 8 , 21 , 27 , 31 However, the majority of these previous studies were limited to a single ESC-R gene or were specific to a particular country and/or source. 8 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Therefore, here we investigated the main ESC-R plasmid types and subtypes at high resolution and at a larger scale, using ESC-R complete genomes from diverse sources and multiple countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ESBL-producing E. coli carrying only the bla CMY-2 gene was reported previously, there was not a clear explanation for this phenomenon (3). IncI1 plasmids carrying the bla CMY-2 gene were shown to widely spread among E. coli (35), and they shared a high degree of sequence similarity when isolated from Enterobacteriaceae with different epidemiological links (36). Unlike other plasmids carrying ESBL genes in this study, insertion sequences were not located proximal to the bla CMY-2 gene.…”
Section: Discussionmentioning
confidence: 99%